Vγ9Vδ2 T cells expanded with vitamin C combined with HMBPP in vitro inhibit intracellular Mycobacterium tuberculosis growth - Shuyan Liu; Shuyan Liu; Guohui Xiao; Wanxin Liang; Su Zhang; Juan Liang; Teng Pan; Shaoxiang Lin; Xiuju Liu; Zhenwen Zhou; Guoliang Zhang (Frontiers in Cellular and Infection Microbiology)
BackgroundMycobacterium tuberculosis (Mtb) presents a significant global health threat, and the existing treatments have notable limitations. Vγ9Vδ2 T cells activated by HMBPP can inhibit the growth of intracellular Mtb. Additionally, vitamin C (VC) promotes the differentiation and proliferation of related T cells. However, it remains uncertain whether VC can enhance the expansion of Vγ9Vδ2 T cells within PBMCs activated by HMBPP and rIL-2, and the underlying mechanism of the inhibitory effect of the expanded T cells on intracellular Mtb has not been elucidated.MethodsVenous blood was collected from healthy individuals, and PBMCs were subsequently isolated. In vitro, Vγ9Vδ2 T cells were selectively expanded with HMBPP, rIL-2, and VC. Flow cytometry was utilized to analyze the purities and phenotypes of Vγ9Vδ2 T cells, while cell counts were performed to determine the total number of viable cells. Magnetic bead sorting was employed to purify Vγ9Vδ2 T cells. Mtb strains were cultured, and macrophage infection models derived from THP1 cells were established. Co-culture experiments were conducted with Mtb-infected macrophages and Vγ9Vδ2 T cells, and the number of intracellular bacteria was quantified through CFU counting. The levels of cytokines were measured using the CBA method and flow cytometry. Statistical analysis was carried out using GraphPad Prism and SPSS software.ResultsVC (70 μM) significantly enhances the expansion of Vγ9Vδ2 T cells within PBMCs during primary HMBPP activation in the presence of rIL-2, with higher induction rates and total cell proliferation. By day 14 of induction, Vγ9Vδ2 T cells expanded with HMBPP, VC, and rIL-2 exhibited the central memory (10-20%) and the effector memory phenotypes (75-90%). Furthermore, these expanded T cells effectively inhibited the growth of intracellular virulent Mtb strain (H37Rv) in a cell-contact-dependent manner. The inhibitory effect was associated with an up-regulated production of TNF-α and IFN-γ, and a down-regulated expression of IL-10 and IL-17A during Mtb infection. ConclusionThis study demonstrates that VC enhances the proliferative expansion of Vγ9Vδ2 T cells in PBMCs primarily stimulated with HMBPP and rIL-2. The expanded Vγ9Vδ2 T cells are capable of effectively inhibiting the growth of virulent H37Rv strain, likely through the secretion of TNF-α and IFN-γ. These findings provide a novel direction for tuberculosis treatment research.